Effects of Rosuvastatin on Apolipoprotein J in Balloon-Injured Carotid Artery in Rats - Yang,Ning (2018)
Abstract Background: Restenosis after percutaneous coronary intervention in coronary heart disease remains an unsolved problem. Clusterin (CLU) (or Apolipoprotein [Apo] J) levels have been reported to be elevated during the progression of postangioplasty restenosis and atherosclerosis. However, its role in neointimal hyperplasia is still controversial. Objective: To elucidate the role Apo J in neointimal hyperplasia in a rat carotid artery model in vivo with or without rosuvastatin administration. Methods: Male Wistar rats were randomly divided into three groups: the control group (n = 20), the model group (n = 20) and the statin intervention group (n = 32). The rats in the intervention group were given 10mg /kg dose of rosuvastatin. A 2F Fogarty catheter was introduced to induce vascular injury. Neointima formation was analyzed 1, 2, 3 and 4 weeks after balloon injury. The level of Apo J was measured by real-time PCR, immunohistochemistry and western blotting. Results: Intimal/medial area ratio (intimal/medial, I/M) was increased after balloon-injury and reached the maximum value at 4weeks in the model group; I/M was slightly increased at 2 weeks and stopped increasing after rosuvastatin administration. The mRNA and protein levels of Apo J in carotid arteries were significantly upregulated after rosuvastatin administration as compared with the model group, and reached maximum values at 2 weeks, which was earlier than in the model group (3 weeks). Conclusion: Apo J served as an acute phase reactant after balloon injury in rat carotid arteries. Rosuvastatin may reduce the neointima formation through up-regulation of Apo J. Our results suggest that Apo J exerts a protective role in the restenosis after balloon-injury in rats.